The Future Trend Of Universities Of Lao People’s Democratic Republic - CHANPHENGXAY, Khamphao; SROINAM , Somkid; INTUSAMITH, Muntana (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
This research aimed to study on the future trend of universities of Lao P.D.R. The research has been used Ethnographic Delphie Futures Research (EDFR) and divided into 3 phases including Study on Higher Education Management theories by In-depth interview with 8 experts, Study on the Future of Universities using Ethnographic Delphi Futures Research with 24 experts and Creating Future of Universities in Lao PDR with 70 experts. Research findings showed that the future trend of universities of Lao PDR (2016-2030) consists of 12 components such as: 1) university management; 2) curriculum and teaching-learning; 3) research; 4) academic services; 5) culture preservation; 6) university’s roles in the community; 7) internal and international cooperation; 8) infrastructure/facility; 9) identity (uniqueness) of university; 10) learners; 11) teachers; and 12) administrators. It was found that the 12 components have 103 sub-components and 84 sub-components have highest possibilities when considering from Arithmetic Mean 4.51–5.00, Median 3.50 up, and Interquartile Range less than or equal 1.50 and 19 sub-components have high possibilities. Conclusion, Components 12 -administrators, components 11- teachers and components 5 - culture preservation respectively have the highest trend and possibility and be the first priority in development.